THE PROBLEMS AND STRATEGIES OF ENGLISH EDUCATION STUDENTS DEALING WITH ONLINE LEARNING IN EXTENSIVE READING SUBJECT - Rahmat Hidayat; Syarifuddin Dollah; Amra Ariyani (Universitas Negeri Makassar, 2022)
This study aims to describe the problems and strategies of English education students dealing with online learning in the extensive reading subject. The researchers apply a qualitative method. To achieve the research objectives, the data collected were in the form of interviews. The population of this study was English Education students academic 2021/2022. The results of the data analysis show that the problem is about the effectiveness of extensive reading subjects in online learning, network availability, learning media, learning method, learning interest, social interaction, and material provided. The strategies related to methods, materials, the use of media, and student interest.